Penicillin-binding protein 4 overproduction increases beta-lactam resistance in Staphylococcus aureus. - Henze, U U (1996)
The Staphylococcus aureus mutant strain PVI selected in vitro for methicillin resistance overexpressed penicillin-binding protein (PBP) 4. In the wild-type parent strain the pbp4 gene was separated by 419 nucleotides from a divergently transcribed abcA locus coding for an ATP-binding cassette transporter. The mutant PVI was shown to have a deletion in the pbp4-abcA promoter region that affected pbp4 transcription but not expression of abcA. Introduction of the pbp4 gene plus the mutant promoter region into different genetic backgrounds revealed that PBP 4 overproduction was sufficient to increase in vitro-acquired methicillin resistance independently of other chromosomal genes. The role of the AbcA transporter in methicillin resistance remained unknown.